2017
DOI: 10.15244/pjoes/60499
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Iron, Manganese, and Copper from Aqueous Solution Using Orange Peel: Optimization, Isothermic, Kinetic, and Thermodynamic Studies

Abstract: The issue of wastewater is becoming more and more important today because of the new European Union laws leading to even stricter norms. Heavy metals belong to some of the negative elements present in wastewater. Their occurrence in wastewater caused by different industrial processes, such as electroplating, metal finishing, metallurgy, chemical production, mining, and production of paper or batteries, raises many questions because of their toxicity even in small concentrations [1].Sorption of heavy metals is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This indicates that the preferred pH for manganese removal is ranges from pH 5 to 7. Higher pH value is not suitable due to precipitate formation of excessive OH ions ( Surovka and Pertile, 2017 ).…”
Section: Adsorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the preferred pH for manganese removal is ranges from pH 5 to 7. Higher pH value is not suitable due to precipitate formation of excessive OH ions ( Surovka and Pertile, 2017 ).…”
Section: Adsorption Processmentioning
confidence: 99%
“…A number of studies have reported the performances of the agricultural waste adsorbents ( Ali, 2017 ; Surovka and Pertile, 2017 ; Bangaraiah, 2018 ; Kumar et al., 2018 ; Leizou et al., 2018 ; Badrealam et al., 2019 ). However, these studies are limited to the laboratory scale, which is unable to estimate the real operational cost.…”
Section: Cost Analysis Of Adsorbentsmentioning
confidence: 99%
“…In recent decades, these studies have focused on the waste derived from the agricultural industry that produces large amounts of waste such as biomass, wheat husks, rice, orange, etc. [2,4,8,9,16,[18][19][20][21][22][23][24][25][26][27][28][29][30]; the use of residues from other industries has also been investigated, such as the case of apatites derived from the bone tissue of animals, which have been used for removal of dyes and metal ions obtaining promising results. The use of apatites in particular hydroxyapatite and brushite for the adsorption of heavy metals such as Cd, Cu, Ni, Pb, Co, Mn, and Fe, to name a few, has already been reported [31][32][33][34][35]; however, in most of the studies carried out, only the process of adsorption of metallic solutions of a single component has been analyzed, so the objective of the present work is to evaluate the capacity of brushite (nDCPD), obtained from bovine bone to remove Ni (II), Co (II), and Cu (II) of aqueous solutions, analyzing the selectivity of removal of metal ions in aqueous solutions with two or three different metals, determining the kinetic models and in equilibrium in which the removal of metals takes place and the structural changes suffered by nDCPD during the development of the different tests.…”
Section: Introductionmentioning
confidence: 99%
“…On average, to produce 1 kg of textile, ~200 L of water is consumed and an average-sized textile mill with a production of about 8000 kg of fabric per day consumed about 1.6 million L water. Moreover, on average, the reported concentrations of biological oxygen demand (BOD 5 ), total solids (TS) and color in textile wastewater are about 6000, 1560 mg/L and 1450-4750 ADMI, respectively [6][7][8]. Importantly, these toxic dyes are creating harmful effects and diseases in residential communities, i.e., allergies, jaundice, heart defects, skin irritation, and tumors.…”
Section: Introductionmentioning
confidence: 99%